Urindogermanisch Wein und Met in den anatolischen Sprachen - Schürr, Diether (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
The existence of wine and mead already in the Proto-Indo-European language is not compatible with the traditional hypothesis of a nomadic origin, but supported by the attestations of these words in the Anatolian languages: Hittite, Luwian in cuneiform texts, Late Luwian in hieroglyphic texts and even Lycian and Carian, albeit only in toponyms. There is no obstacle to supposing that the agrarian Proto-Indo-Europeans did already domesticate grapes and bees, like Anatolians and like Mycenean Greeks in the second millenium BC, and the loan of the word for wine into West-Semitic is a strong argument for this.